Hukum Islam: Hakikat dan Tujuan Pemberlakuan - Saidurrahman, Saidurrahman (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2009)
My main intention of writing this article howefer is very simple. Mainly I want to invite participants to paya greater attention  on  doing  further  research  on  Islamic  law  from philosophy  point  of  view.  Most  of  the  time  Islamic  law  is studied  merely  based  on  teology  perspective.  Islamic  law philosophy  questioned  problems  that  is  beyond  of  ordinary law, critically questioned absolute paradigm in the Islamic law and constructively tried to unify the branchs of Islamic law in the  whole  of  Islamic  law  system  which  is  unseparable.  So Islamic  law  philosophy  offered  questions  about  the  exact meaning and the real goal of Islamic law.